The Kumagai Method: Feeding Techniques Using the Pigeon Baby Cleft Palate Bottle - Ueki, Shingo; Kumagai, Yukari; Hirai, Yumi; Nagatomo, Eri; Miyauchi, Shoko; Inoue, Takuro; An, Qi; Tashiro, Eri; Miyata, Junko (Nursing reports (Pavia, Italy), 2024)
Background/Objectives: This study aimed to identify the P-bottle feeding techniques systematically organized by Ms. Kumagai, an expert in nursing care for children with a cleft lip and/or palate (CLP), which were developed as she gained expertise in feeding affected children. Methods: We recruited three nurses who had mastered the Kumagai method for feeding with a P-bottle. Through analysis of participants’ voices and videos during interviews, we focused on aspects such as dealing with a closed mouth, inserting the nipple in cases of unilateral and bilateral CLP, dealing with the child’s movements after insertion, and key considerations when squeezing the bottle. Results: The interview analyses revealed numerous techniques used by nurses to manage the difficulties encountered while feeding children, ensuring successful provision of nourishment. Specifically, the nurses employed techniques such as placing the nipple along the midline of the child’s tongue and varying the application of force on the nipple depending on the cleft type. The nurses reported that the objectives of these techniques were to prevent ulcer formation and encourage the use of the tongue, simulating original feeding movements. Conclusions: We explored feeding techniques and the management of associated challenges. Our results suggest that the “Kumagai Method” could be valuable in improving feeding practices.